Novel PHEX Gene Mutations in Two Taiwanese Patients with Hypophosphatemic Rickets - 周言穎(Yen-Yin Chou); 趙曉秋(Sheau-Chiou Chao); 蔡尚均(Shang-Chun Tsai); 林秀娟(Shio-Jean Lin) (Journal of the Formosan Medical Association, 2005)
Hypophosphatemic rickets is a genetic disorder commonly associated with renal phosphate wasting and bone deformities. The PHEX gene (phosphate regulating gene with homologies to endopeptidases on the X chromosome) encodes a 749-amino acid protein that putatively consists of an intracellular, transmembrane, and extracellular domain. PHEX mutations have been observed in 60-80% of hypophosphatemic rickets patients. In this study, we report 2 de novo novel mutations in 2 Taiwanese girls with clinical characteristics of hypophosphatemic rickets. The presenting phenotype of lower extremity deformities and short stature was suggestive of the diagnosis. Primers flanking 22 exons were used to amplify DNA by polymerase chain reaction. The results by direct DNA sequencing of case 1 revealed a C to T transition changing glutamine at codon 224 in exon 6 to a stop codon (Q224X). The result of case 2 showed a 2-base pair deletion (2090delGA) and resulted in a frameshift and premature termination of codon (PTC+19aa). Both mutations presumably result in a truncated protein, leading to loss of function of PHEX. This is the first report of PHEX gene mutation in the Taiwanese population.